Total Fat Content and Fatty Acid Profile of Fine-Aroma Cocoa From Northeastern Peru - Oliva-Cruz M. (2021)
The authors would like to acknowledge the funding of the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FONDECYT) through the Project with Contract N? 026-2016 Círculo de Investigación para la Innovación y el fortalecimiento de la cadena de valor del cacao nativo fino de aroma en la zona nor oriental del Perú-CINCACAO, and the support and execution of this project by the Instituto de Investigación para el Desarrollo Sustentable de Ceja de Selva (INDES-CES).